CD72-semaphorin3A axis: A new regulatory pathway in systemic lupus erythematosus. Issue 134 (January 2023) - Eiza, Nasren; Sabag, Adi D.; Kessler, Ofra; Neufeld, Gera; Vadasz, Zahava
Abstract: CD72 is a regulatory co-receptor on B cells, with a role in the pathogenesis of systemic lupus erythematosus (SLE) in both human and animal models. Semaphorin3A (sema3A) is a secreted member of the semaphorin family that can reconstruct B cells' regulatory functions by upregulating IL-10 expression and inhibiting the pro-inflammatory activity of B and T cells in autoimmune diseases. The aim of our present study was to identify a new ligand for CD72, namely sema3A, and exploring the signal transduction pathways following its ligation in B cells. We established that CD72 functions as sema3A binding and signal-transducing receptor. These functions of CD72 are independent of neuropilin-1 (NRP-1) (the known sema3A receptor). We discovered that sema3A induces the phosphorylation of CD72 on tyrosine residues and the association of CD72 with SHP-1 and SHP-2. In addition, the binding of sema3A to CD72 on B cells inhibits the phosphorylation of STAT-4 and HDAC-1 and induces the phosphorylation of p38-MAPK and PKC-theta in B-cells derived B-lymphoblastoid (BLCL) cells, and in primary B-cells isolated from either healthy donors or SLE patients. We concluded that sema3A is a functional regulatory ligand for CD72 on B cells. The sema3A-CD72 axis is a crucial regulatory pathway in the pathogenesis of autoimmune and inflammatory diseases namely SLE, and modulation of this pathway may have a potential therapeutic value for autoimmune diseases. Graphical abstract: In B cells, semaphorin3A binds CD72, leading to tyrosine residues phosphorylation and the association of SHP-1/2, which inhibits the STAT-4 and HDAC-1 phosphorylation and increased phosphorylation of p38-MAPK and PKC-theta. Image 1 Highlights: CD72 is highly valued as a regulatory molecule on B cells. Semaphorin3A is demonstrated to be a specific regulatory ligand for CD72. Semaphorin3A binding to CD72 is crucial for the maintenance of self-tolerance. Semaphorin3A-CD72 axis is a potential therapeutic target in the management of SLE.